2016
DOI: 10.3390/nu8120768
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 Status among Pregnant Women in the UK and Its Association with Obesity and Gestational Diabetes

Abstract: Background: To evaluate vitamin B12 and folate status in pregnancy and their relationship with maternal obesity, gestational diabetes mellitus (GDM), and offspring birthweight. Methods: A retrospective case-control study of 344 women (143 GDM, 201 no-GDM) attending a district general hospital and that had B12 and folate levels measured in the early 3rd trimester was performed. Maternal history including early pregnancy body mass index (BMI) and neonatal data (birthweight, sex, and gestational age) was recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
80
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 34 publications
9
80
2
1
Order By: Relevance
“…The findings of this study are consistent with previous studies showing that a low vitamin B 12 concentration may be an independent risk factor for GDM. [10][11][12] The above findings of the present and previous studies show that high folate and low vitamin B 12 can interfere with the onset of GDM. Therefore, a new indicator, the folate: vitamin B 12 ratio, representing high folate and/or low vitamin B 12 , was calculated to explore the effects of B vitamin imbalance on GDM risk.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The findings of this study are consistent with previous studies showing that a low vitamin B 12 concentration may be an independent risk factor for GDM. [10][11][12] The above findings of the present and previous studies show that high folate and low vitamin B 12 can interfere with the onset of GDM. Therefore, a new indicator, the folate: vitamin B 12 ratio, representing high folate and/or low vitamin B 12 , was calculated to explore the effects of B vitamin imbalance on GDM risk.…”
Section: Discussionsupporting
confidence: 76%
“…[6][7][8][9] Recently, the role of folate and vitamin B 12 on the development of GDM has emerged as a field of interest. [10][11][12] Folate and vitamin B 12 are metabolically entwined during 1-carbon metabolism. Both serve as cofactors in the synthesis of methionine from homocysteine (Hcy).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a few studies reported that serum folate concentrations were not associated with GDM risk (Krishnaveni et al, 2009;Sukumar et al, 2016). For example, Sukumar et al (2016) Note: Values are expressed as numbers with percentages (%). All values are ORs (95% CIs) and adjusted for maternal age, BMI at enrollment, gestational weeks at enrollment, gestational weeks at delivery, and infant gender (excluded the stratified factor in each stratum) critical time windows in pregnancy make comparisons challenging.…”
Section: Discussionmentioning
confidence: 99%
“…authors (14)(15)(16)(17)(18)(19)(20)(21) . However, to date, no study has evaluated the association of serum B 12 levels with excessive body weight using a 'gold standard' method to evaluate body adiposity such as dual-energy X-ray absorptiometry (DXA).…”
mentioning
confidence: 99%